Báo cáo tiếp thu, chỉnh lý, hoàn thiện dự thảo Luật Đấu thầu (sửa đổi) (kèm theo Dự thảo Luật Đấu thầu sửa đổi) - Chính phủ (2023)
Toàn văn Báo cáo tiếp thu, chỉnh lý, hoàn thiện dự thảo Luật Đấu thầu (sửa đổi) (kèm theo Dự thảo Luật Đấu thầu sửa đổi).